IMPROVING STUDENT'S LEARNING OUTCOMES USING THE CONTEXTUAL LEARNING MODEL ON LISTENING COMPETENCY IN INDONESIAN LESSONS - lilis sulistyaningrum ningrum (Journal of Education Technology and Inovation, 2022)
This study applies a contextual learning model in order to improve learning outcomes in listening to learning so that students have perfect Indonesian language skills, learning learning concepts that help teachers relate the Indonesian language material they teach to real environmental situations and encourage students to make connections between language knowledge that they teach. possessed by the application of language in everyday life Classroom action research activities were carried out for three cycles. The learning outcomes obtained from the researchers in the first cycle were with an average of 58% (less) or only 24 students who completed or 59% while 41% or as many as 15 students were still incomplete and scored below the KKM (75). Then in the second cycle the average increased by obtaining 73% or students completed as many as 30 students or 73%. Then in the third cycle there was a significant increase, namely the average obtained was 94% or as many as 39 students who scored above the KKM (75). In addition, the activity of class XI students of the Department of Administration 2 during learning activities by applying contextual learning experienced an increase in listening material, in the first cycle it reached 57.5%, the second cycle increased to 72.86% and in the third cycle it increased again to 93.62 % with very good category. This indicates that the student's response to contextual learning is included in the interested category.